Different feeding patterns affect meat quality of Tibetan pigs associated with intestinal microbiota alterations - Zhu, Yanbin; Cidan-yangji; Sun, Guangming; Luo, Chengzeng; Duan, Jiujun; Shi, Bin; Ma, Teng; Tang, Shanlong; Zhong, Ruqing; Chen, Liang; Basang-wangdui; Zhang, Hongfu (Frontiers in Microbiology, 2022)
This study aimed to investigate the effects of different feeding patterns on meat quality, gut microbiota and its metabolites of Tibetan pigs. Tibetan pigs with similar body weight were fed the high energy diets (HEP, 20 pigs) and the regular diets (RFP, 20 pigs), and free-ranging Tibetan pigs (FRP, 20 pigs) were selected as the reference. After 6 weeks of experiment, meat quality indexes of semitendinosus muscle (SM) and cecal microbiota were measured. The results of meat quality demonstrated that the shear force of pig SM in FRP group was higher than that in HEP and RFP groups (p < 0.001); the pH-value of SM in HEP pigs was higher at 45 min (p < 0.05) and lower at 24 h (p < 0.01) after slaughter than that in FRP and RFP groups; the SM lightness (L* value) of FRP pigs increased compared with RFP and HEP groups (p < 0.001), while the SM redness (a* value) of FRP pigs was higher than that of RFP group (p < 0.05). The free fatty acid (FA) profile exhibited that the total FAs and unsaturated FAs of pig SM in HEP and RFP groups were higher than those in FRP group (p < 0.05); the RFP pigs had more reasonable FA composition with higher n-3 polyunsaturated FAs (PUFAs) and lower n-6/n-3 PUFA ratio than HEP pigs (p < 0.05). Based on that, we observed that Tibetan pigs fed high energy diets (HEP) had lower microbial α-diversity in cecum (p < 0.05), and distinct feeding patterns exhibited a different microbial cluster. Simultaneously, the short-chain FA levels in cecum of FRP and RFP pigs were higher compared with HEP pigs (p < 0.05). A total of 11 genera related to muscle lipid metabolism or meat quality, including Alistipes, Anaerovibrio, Acetitomaculun, etc., were identified under different feeding patterns (p < 0.05). Spearman correlation analysis demonstrated that alterations of free FAs in SM were affected by the genera Prevotellaceae_NK3B31_group, Prevotellaceae UCG-003 and Christensenellaceae_R-7_group (p < 0.05). Taken together, distinct feeding patterns affected meat quality of Tibetan pigs related to gut microbiota alterations.